Web Service untuk Integrasi Data Materi Pelajaran Sekolah Menengah Pertama (SMP) Secara Terdistribusi - Astika Ayuningtyas; Yuliani Indrianingsih (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
The National Education Standards Agency's (BSNP) curriculum requires in principle the active participation of students in collecting information from various media, including one on the Internet. The role of schools, especially teachers, in providing sources of materials is also very necessary. The Internet is one of the means of information essential to the learning process. Therefore, setting up a digital hardware service network can be an effective learning tool. Digital hardware services can be mutually integrated between schools to obtain a variety of physical resources. The existence of a web service can integrate subject data into each school and can provide distributed information to many providers and service users according to the needs of each user. The Web service is different from a search engine system that does not provide the necessary data integration on hardware service systems that connect data between schools to be distributed to users according to their needs. The web service technology that is built is able to integrate the subject's service material and can be distributed to many users with different needs.